2023
DOI: 10.3390/lubricants11010018
|View full text |Cite
|
Sign up to set email alerts
|

Tribology Performance of Polyol-Ester Based TiO2, SiO2, and Their Hybrid Nanolubricants

Abstract: The tribology properties of TiO2/POE, SiO2/POE and TiO2-SiO2/POE nanolubricants were investigated for an automotive air-conditioning system with an electrically-driven compressor (EDC). A two-step preparation method was used in dispersing TiO2 and SiO2 nanoparticles into Polyol-ester (POE)-based lubricant at different volume concentrations of 0.01 to 0.1%. The coefficient of friction (COF) and wear scar diameter (WSD) were investigated using a Koehler four-ball tribo tester and microscopes. For the TiO2/POE, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The absence of visual alterations or settling further affirms the suitability of the formulation for potential applications in tribological systems. These findings contribute evidence of the successful integration and long-term stability of nanoparticles within the nanolubricant, paving the way for enhanced tribological performance and extended service life 41 , 42 .…”
Section: Resultsmentioning
confidence: 71%
“…The absence of visual alterations or settling further affirms the suitability of the formulation for potential applications in tribological systems. These findings contribute evidence of the successful integration and long-term stability of nanoparticles within the nanolubricant, paving the way for enhanced tribological performance and extended service life 41 , 42 .…”
Section: Resultsmentioning
confidence: 71%
“…Nevertheless, the surface roughness of the titanium foils increased gradually when further increasing the concentration of TiO 2 nanoparticles from 3.0 wt.% to 9.0 wt.%. The phenomenon can be explained by the smaller contact area due to the aggregation of nanoparticles [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the methods described above to modify PIs, the researchers also explored other methods. SiO 2 nanoparticles have extensive applications in promoting the thermal, mechanical and tribological properties of polymers (Hamisa et al , 2023; Ismail et al , 2022). It has been reported that the in situ polymerization method was used to prepare nanocomposites by incorporating nano-SiO 2 into PI matrix (Zhao et al , 2016).…”
Section: Progress In Tribological Research Of Polyimide Compositesmentioning
confidence: 99%